Zmiany w uwarunkowaniach prawno- administracyjnych dotyczących bezpośrednich inwestycji zagranicznych w Polsce - Stawicka, Magdalena (Changes in legal-administrative conditions relating direct foreign investment's inflow to Poland, 2006)
The purpose of this article is to make a survey of legal-administrative conditions enabling the inflow of foreign capital into Poland. It is important to promote investment and attract capital to sectors which require refinancing. Thanks to the presence of foreign investments, Poland strengthened the position in international conversion trade. Poland should further create favourable conditions for foreign investors and increase the inflow of direct foreign investments. To this aim, it is necessary to liberalize the Polish law and adapt it to meet expectations of foreign businessmen. New acts concerning foreign capital have been passed for many years. However Polish law is still disconnected, often contradictory, and it undergoes changes very often.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 356-362